2018
DOI: 10.3390/molecules23092255
|View full text |Cite
|
Sign up to set email alerts
|

Gold Catalyzed Multicomponent Reactions beyond A3 Coupling

Abstract: The preparation of complex architectures has inspired the search for new methods and new processes in organic synthesis. Multicomponent reactions have become an interesting approach to achieve such molecular diversity and complexity. This review intends to illustrate important gold-catalyzed examples for the past ten years leading to interesting skeletons involved in biologically active compounds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(17 citation statements)
references
References 105 publications
0
14
0
Order By: Relevance
“…Shaabani and co‐workers put forward a three‐component strategy for the synthesis of 1,6‐dihydropyrazine‐2,3‐dicarbonitrile (Scheme 64) and 3,4‐dihydroquinoxalin‐2‐amine (Scheme 65). [ 21 ] The reaction of 2,3‐diaminomaleonitrile 158 , acetone and cyclohexyl isocyanide 16 in presence of iron catalyst in 6 ml water resulted in the formation of the desired product 1,6‐dihydropyrazine‐2,3‐dicarbonitrile 159 with a maximum of 93% yield. The reaction of o ‐phenylene diamine with acetone and cyclohexyl isocyanide delivered 3,4‐dihydroquinoxalin‐2‐amine 161 in 92% yield.…”
Section: Classificationmentioning
confidence: 99%
See 2 more Smart Citations
“…Shaabani and co‐workers put forward a three‐component strategy for the synthesis of 1,6‐dihydropyrazine‐2,3‐dicarbonitrile (Scheme 64) and 3,4‐dihydroquinoxalin‐2‐amine (Scheme 65). [ 21 ] The reaction of 2,3‐diaminomaleonitrile 158 , acetone and cyclohexyl isocyanide 16 in presence of iron catalyst in 6 ml water resulted in the formation of the desired product 1,6‐dihydropyrazine‐2,3‐dicarbonitrile 159 with a maximum of 93% yield. The reaction of o ‐phenylene diamine with acetone and cyclohexyl isocyanide delivered 3,4‐dihydroquinoxalin‐2‐amine 161 in 92% yield.…”
Section: Classificationmentioning
confidence: 99%
“…disclosed the synthesis of tetrahydro‐1 H ‐1,5‐benzodiazepine‐2‐carboxamide 167 (Scheme 68) and 4,5,6,7‐tetrahydro‐1 H ‐1,4‐diazepine‐5‐carboxamide 168 (Scheme 69) by using natural wool sulfonic acid (wool‐SO 3 H) and wool‐supported Fe 3 O 4 nanoparticles (nano‐Fe 3 O 4 @wool) as catalyst. [ 21 ] The substrate scope exploration using different amines and carbonyl compounds revealed that these have reacted well to give the desired products in good to excellent yields.…”
Section: Classificationmentioning
confidence: 99%
See 1 more Smart Citation
“…Many of them highlight the advances in the synthesis of propargylamines, [23] including the asymmetric version of the reaction [17g,23c,24] . Besides, a number of reviews are available on the employment of particular catalysts, e. g ., gold, [25] nanoparticles [26] and so on. Applications of a particular type of starting materials are considered in the review by Liu [27] .…”
Section: Introductionmentioning
confidence: 99%
“…Multicomponent reactions (MCRs), defined as one-pot processes in which three or more accessible starting materials are incorporated into a single product without isolating the intermediates, have gained importance in academia and industry [1,2,3,4]. Multicomponent reactions provide numbers of valuable conceptual and synthetic advantages such as sustainability, operational simplicity, and high convergence.…”
Section: Introductionmentioning
confidence: 99%